1999 Queensland years 3, 5 and 7 testing program : practice and testing materials - Queensland School Curriculum Council ([Brisbane] : Queensland School Curriculum Council, 1999)
"A package containing the information and test material that was sent to all Queensland schools participating in the 1999 Queensland Years 3, 5 and 7 testing program"-- List
List of items in the package included.
Title from cover of the portifolio.
Keywords: Educational tests and measurements -- Queensland; Mathematical ability -- Testing; Literacy -- Queensland; Numeracy -- Queensland; Reading -- Ability testing -- Queensland